Rafflesia harjatii (Rafflesiaceae) sp. nov., a new species from East Kalimantan, Indonesia - Mahyuni, Ridha; Susatya, Agus; Sudarmono; Latifah, Dian; Smits, Willie; Priyadi, Arief (Penerbit Universiti Kebangsaan Malaysia, 2026)
The vast and difficult to access region of Kalimantan is known to the home of eight species of Rafflesia including the arguable taxonomy status of three incomplete species. Flowering events of Rafflesia have been reported from East Kalimantan. However, their taxonomy statuses have not been verified. This information leads to the National Research and Innovation Agency (BRIN) to launch an initiative exploration investigating the taxonomy of Rafflesia in East Kalimantan. This exploration involved morphological comparisons and DNA sequencing analysis to determine the taxonomic status of the flowering Rafflesia found at ITCI-Kartika Utama Timber concession (ITCI-KU) in Sepaku, Penajam Paser Utara, East Kalimantan. The morphological comparisons between Rafflesia species from ITCI-KU and the eight Rafflesia recorded in Kalimantan showed the consistent differences with regard to the absence of windows, a single anulus, polymorphic processi, toadstool, and branched swollen apex of ramenta structures. It shares similarities with R. tengku-adlinii from Sabah, Malaysia, and Rafflesia aurantia from Luzon, Philippines, particularly regarding the absence of window structures, and the size of flowering. However, it differs from these two species in several diagnostic characters including the diaphragm openness, the structure and arrangement of ramenta, processus, column, groove, and annulus. The result of DNA analysis also confirmed that the Rafflesia from ITCI-KU differs from the all reported Rafflesia from Kalimantan. Thus, it has designated as Rafflesia harjatii sp. nov. An identification key to distinguish species of Rafflesia in Kalimantan is also provided.